Physicochemical characteristics of fine coarse particles in indoor building - Teh, Joe Ean (2015)
An experimental study was conducted to investigate the physicochemical characteristics of fine and coarse particles as the major pollutants that may post risks to human health in the indoor workplace building of chemical company which located in Gebeng, Kuantan. The objectives of this study are to measure the concentration level of particles, to assess the heavy metals concentration which associated with particles, and to investigate the relationship of the concentration level of particles in the indoor and outdoor workplace building of chemical company. A walkthrough observation was conducted in order to study the layout building, to define the exposure zones for conducting sampling in the building, to obtain the basic information on the factors that may affect indoor air quality and identifying the sources of the potential contaminants. The concentration level of particles was collected by using a very fast response hand-held instrument and the heavy metal which associated with fine and coarse particles was analysed by using Inductively Coupled Plasma- Mass Spectrometry (ICP-MS). The results of concentration level of particles was compared with the WHO Guideline of Indoor Air Quality for Particulate Matter and US-EPA Standard for particulate matter. It shows that the concentration level of fine particles at location B of workplace building of chemical company is not complied with WHO Guideline of Indoor Air Quality for Particulate Matter. In addition, the concentration levels of coarse particles at three points A, B, and C are not complied with both WHO guideline and US-EPA Standard. While only the concentration level of coarse particle at location D is complied with the standard limits that stated in US-EPA guidelines. For the outdoor environment, both fine and coarse particles concentration levels are complied with the National Ambient Air Quality Standard (NAAQS). Apart from this, it was found that six heavy metals such as Al, Si, Se, Co, Ba, and Ga which associated with fine and coarse particles in the indoor and outdoor environment of the workplace building of chemical company. Some control measures were proposed in order to minimize the concentration level of fine and coarse particles in the indoor building such as removing the pollutants by houseplants, isolating the photocopier machine and printers in a good ventilation room, vacuuming cleaning frequently with correct way, exchange the filter of air condition from time to time, and conducting IAQ assessment frequently.